Changes in nitrergic and tachykininergic pathways in rat proximal colon in response to chronic treatment with otilonium bromide. Issue 7 (30th April 2015) - Cipriani, G.; Gibbons, S. J.; Saravanaperumal, S. A.; Malysz, J.; Sha, L.; Szurszewski, J. H.; Linden, D. R.; Evangelista, S.; Faussone‐Pellegrini, M. S.; Vannucchi, M. G.; Farrugia, G.
Abstract Background Otilonium bromide (OB) is used as a spasmolytic drug in the treatment of the functional bowel disorder irritable bowel syndrome. Although its acute effects on colonic relaxation are well‐characterized, little is known about the effects of chronic administration of OB on enteric neurons, neuromuscular transmission, and interstitial cells of Cajal (ICC), key regulators of the gut function. Methods Adult Sprague–Dawley rats were treated with OB in drinking water at a dose of 2 mg/kg for 30 days. The colons of OB‐treated and age‐matched control rats were studied by confocal immunohistochemistry to detect immunoreactivity (IR) in myenteric plexus neurons for nitrergic and tachykininergic markers, and also by microelectrode electrophysiology. Key Results Using immunohistochemistry, chronic OB administration did not change total neuron number, assessed by anti‐Hu IR, but resulted in a significant increase in NK1 receptor positive neurons, a decrease in neuronal nitric oxide synthase expressing neurons, and a reduction in volume of substance P in nerve fibers in the myenteric plexus. Chronic OB administration potentiated inhibitory and excitatory junction potentials evoked by repetitive electrical field stimulation. The various types of colonic ICC, detected by Kit IR, were not altered nor were slow waves or smooth muscle membrane potential. Conclusions & Inferences Chronic treatment with OB caused significant changes in the nitrergic and tachykinergic components of the myenteric plexus and in both inhibitory and excitatory neurotransmission in the rat colon.